2022
DOI: 10.3389/fcimb.2022.845580
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Membrane Fusion in Neurodegenerative Disorders

Abstract: A growing body of epidemiological and research data has associated neurotropic viruses with accelerated brain aging and increased risk of neurodegenerative disorders. Many viruses replicate optimally in senescent cells, as they offer a hospitable microenvironment with persistently elevated cytosolic calcium, abundant intracellular iron, and low interferon type I. As cell-cell fusion is a major driver of cellular senescence, many viruses have developed the ability to promote this phenotype by forming syncytia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 343 publications
(400 reference statements)
2
10
0
Order By: Relevance
“…Recent studies have reported that STRs can increase the risk of schizophrenia and autism spectrum disorder (ASD), indicating that these sequences play a major role not only in monogenic but also in polygenic disorders [16,17]. Indeed, the findings of Ambati BK, et al are in line with our own studies that connected FCS to pathological cell-cell fusion, neurodegeneration, and psychopathology [18,19]. As COVID-19 mRNA vaccines elicit the expression of full-length S antigen (including the FCS), these therapeutics may promote pathological syncytia [20].…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Recent studies have reported that STRs can increase the risk of schizophrenia and autism spectrum disorder (ASD), indicating that these sequences play a major role not only in monogenic but also in polygenic disorders [16,17]. Indeed, the findings of Ambati BK, et al are in line with our own studies that connected FCS to pathological cell-cell fusion, neurodegeneration, and psychopathology [18,19]. As COVID-19 mRNA vaccines elicit the expression of full-length S antigen (including the FCS), these therapeutics may promote pathological syncytia [20].…”
supporting
confidence: 73%
“…
3(4)-40 other hand, fragile X mental retardation protein (FMRP), the product of FMR1 gene, was demonstrated to target influenza and Zika viruses, while metabotropic glutamate 5 receptor (mGluR5) inhibitors, commonly utilized in FXS, often ameliorate SARS-CoV-2 symptoms, indicating a two-way street between viral infections and TRDs [13][14][15].Recent studies have reported that STRs can increase the risk of schizophrenia and autism spectrum disorder (ASD), indicating that these sequences play a major role not only in monogenic but also in polygenic disorders [16,17]. Indeed, the findings of Ambati BK, et al are in line with our own studies that connected FCS to pathological cell-cell fusion, neurodegeneration, and psychopathology [18,19]. As COVID-19 mRNA vaccines elicit the expression of full-length S antigen (including the FCS), these therapeutics may promote pathological syncytia [20].
…”
supporting
confidence: 66%
“…In addition, iron dyshomeostasis and excessive pTau, documented in HAND, AD, and traumatic brain injury (TBI), implicate ELS in these pathologies ( Canzoniero and Snider, 2005 ; Ravi et al, 2016 ; Cantres-Rosario et al, 2019 ; Hook et al, 2020 ; Nagakannan et al, 2021 ; Pedrera et al, 2021 ). Furthermore, as pTau acts as a cell-penetrating peptide, it may trigger cell-cell fusion and senescence, probably accounting for the accelerated aging and early development of AD in PLWH on long term cART ( Ferrell and Giunta, 2014 ; Veloria et al, 2017 ; Osorio et al, 2022 ). Along these lines, HIV infected macrophages were shown to enter the brain and secrete neurotoxic CatB, triggering premature senescence, ferroptosis and FIN ( Cantres-Rosario et al, 2019 ).…”
Section: Ferroptosis and The Endosomal-lysosomal Systemmentioning
confidence: 99%
“…Indeed, senescent cells offer a hospitable microenvironment with persistently elevated cytosolic calcium, abundant intracellular iron, and low interferon type I. As a result, in infected hosts, virus-induced immune dysfunction and premature cellular senescence may predispose to aging-related disease such as neurodegenerative disorders ( Osorio et al 2022 ). Similarly, some viruses have been proposed to hijack the senescent machinery within the infected cell to downregulate the interferon pathway, to promote viral packaging and ultimately to enhance viral replication within the cell ( Kim et al 2016 ; Kelley et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%